2022
DOI: 10.1021/acschembio.2c00032
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrically Regioselective Homodimerization Depends on the Subcellular Colocalization of Laccase/Fasciclin Protein in the Biosynthesis of Phlegmacins

Abstract: Phlegmacins are homodimeric dihydroanthracenone natural products featuring two torosachrysone monomers unsymmetrically conjugated by 7,10′-coupling. Herein, we report the identification and characterization of the biosynthetic gene cluster of phlegmacins in ascomycete Talaromyces sp. F08Z-0631. On the basis of the heterologous reconstitution of the phlegmacin pathway in Aspergillus oryzae, we demonstrated an unprecedented laccase-involved unsymmetrically regioselective oxidative coupling reaction. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, it shows no sequence identity (Table S4), implying their different functions to diversify class B PQs. Based on the above data and previous studies, [15,18b,20b] the biosynthetic pathways of all typical class B PQs are proposed (Figure 4A).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…However, it shows no sequence identity (Table S4), implying their different functions to diversify class B PQs. Based on the above data and previous studies, [15,18b,20b] the biosynthetic pathways of all typical class B PQs are proposed (Figure 4A).…”
Section: Resultsmentioning
confidence: 70%
“…It seems that the addition of CTB11 has no contribution for the formation of ent ‐ 3 in our assay (Figure 3A, x and xi). Recent studies have revealed that fasciclin proteins are membrane proteins and only the subcellular colocalization with laccase could carry out the oxidative dimerization for PQs biosynthesis [20b] . Thus, it indicates that our truncated version of CTB11 loses its regio‐ and stereo‐selective function.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Similar to that previously described (Zhao et al 2022 ), transformation of A. oryzae NSAR1 was performed by a protoplast–polyethylene glycol method. The spore suspension of A. oryzae NSAR1 was seeded in 10 mL DPY medium (2% dextrin, 1% polypeptone, 0.5% yeast extract, 0.05% MgSO 4 ·7H 2 O, 0.5% KH 2 PO 4 , without pH adjustment), cultured for 2 days at 30 °C and 150 rpm, and then transferred into 100 mL DPY medium for another day.…”
Section: Methodsmentioning
confidence: 99%